"Keep on ROCKIn": Repurposed ROCK inhibitors to boost corneal endothelial regeneration - Vercammen, Hendrik; Ondra, Martin; Kotulova, Jana; De La Hoz, Edgar Cardenas; Witters, Charissa; Jecmenova, Katerina; Le Compte, Maxim; Deben, Christophe; Ní Dhubhghaill, Sorcha; Koppen, Carina; Hajdúch, Marián; Van den Bogerd, Bert (Biomedicine & pharmacotherapy, 2024)
The global shortage of corneal endothelial graft tissue necessitates the exploration of alternative therapeutic strategies. Rho-associated protein kinase inhibitors (ROCKi), recognized for their regenerative potential in cardiology, oncology, and neurology, have shown promise in corneal endothelial regeneration. This study investigates the repurposing potential of additional ROCKi compounds. Through screening a self-assembled library of ROCKi on B4G12 corneal endothelial cells, we evaluated their dose-dependent effects on proliferation, migration, and toxicity using live-cell imaging. Nine ROCKi candidates significantly enhanced B4G12 proliferation compared to the basal growth rate. These candidates were further assessed for their potential to accelerate wound closure as another indicator for tissue regeneration capacity, with most demonstrating notable efficacy. To assess the potential impact of candidate ROCKi on key corneal endothelial cell markers related to cell proliferation, leaky tight junctions and ion efflux capacity, we analyzed the protein expression of cyclin E1, CDK2, p16, ZO-1 and Na+/K+-ATPase, respectively. Immunocytochemistry and western blot analysis confirmed the preservation of corneal endothelial markers post-treatment with ROCKi hits. However, notable cytoplasm enlargement and nuclear fragmentation were detected after the treatment with SR-3677 and Thiazovivin, indicating possible cellular stress. In compared parameters, Chroman-1 at a concentration of 10 nM outperformed other ROCKi, requiring significantly 1000-fold lower effective concentration than established ROCKi Y-27632 and Fasudil. Altogether, this study underscores the potential of repurposing ROCKi for treating corneal endothelial dysfunctions, offering a viable alternative to conventional grafting methods, and highlights Chroman-1 as a promising candidate structure for hit-to-lead development.
Keywords: rohovkový endotel; Animals; proliferace buněk; buněčné linie; inhibitory proteinkinas; kinázy asociované s rho; Regeneration; lidé; Endothelial Cells; Cell Line; pohyb buněk; regenerace; Endothelium, Corneal; Protein Kinase Inhibitors; Drug Repositioning; endoteliální buňky; Cell Proliferation; Cell Movement; zvířata; rho-Associated Kinases; přehodnocení terapeutických indikací léčivého přípravku; Humans